FAKTOR-FAKTOR KEJADIAN SKABIES PADA SANTRI DI PONDOK PESANTREN NURUL ISLAM DESA KARANGJATI SAMPANG CILACAP - Dita Yudiasari; Ragil Setiyabudi (Universitas Fort De Kock, 2021)
Abstract Background: Scabies is a contagious skin disease. Sarcoptes scabiei is a scabies mite that causes inflammation, an itchy reaction and a rash on the skin. Factors that play a role in scabies transmission include knowledge, attitudes, personal hygiene, economic status, and gender. Objective: To find out the factors which cause scabies in students at Nurul Islam Islamic Boarding School in Karangjati Village, Sampang Cilacap. Method: The type of this research was an analytic observation method with a case-control approach. The sampling technique in this research was the total sampling technique, with 25 samples for case samples (scabies) and 35 samples for case-control samples (nonscabies). The data were analyzed using the Chi-Square test with Odd ratios and logistic regression. Results: Chi-square test results showed a relationship between knowledge (p = 0.017; OR = 6.417), attitude (p = 0.002; OR = 6,000), personal hygiene (p = 0.029; OR = 8,500), economic status (p = 0.015; OR = 9,600), and gender (p = 0.004; OR = 4,929) with the occurrence of scabies at Nurul Islam Islamic Boarding School in Karangjati Village. Logistic regression analysis showed that attitude was the most dominant variable related to the occurrence of scabies (p = 0.008 ExpB = 6.835). Conclusion: There is a relationship between knowledge, attitudes, personal hygiene, economic status and gender in students with the occurrence of scabies at Nurul Islam Islamic Boarding School in Karangjati Village. The most dominant factor with the incidence of scabies is the attitude of students.